Metode pembelajaran konvensional: Drill, hafalan dan demonstrasi - Fikri, Muhammad Ilham Ali (Maliki Interdisciplinary Journal, 2024)
This study discusses conventional teaching methods, which include drill, memorization, and demonstration methods, and their application in the teaching and learning process. The drill method emphasizes repetition to improve students’ skills, while the memorization method focuses on the ability to recall information. The demonstration method is used to directly show concepts or skills to students. Although these conventional methods have long been utilized in education, this study aims to evaluate their effectiveness in the more dynamic modern educational era. The study also identifies the strengths and weaknesses of each method and their impact on students’ learning outcomes. The findings indicate that drill and memorization methods tend to be effective in enhancing basic skills but are less supportive of critical thinking development. On the other hand, the demonstration method helps students understand material in a more visual and practical manner. The recommendation from this study is to adopt more varied teaching methods, tailored to the needs and characteristics of the students, in order to achieve optimal learning outcomes.